'A Past That Will Not Pass': Italian cinema and the return to the 1970s. (20th November 2012) - O'Rawe, Catherine
This article examines two films, Pasolini: un delitto italiano/Who Killed Pasolini? (1995) by Marco Tullio Giordana and La prima linea/The Front Line (2009) by Renato De Maria, in relation to their revisiting of traumatic and unresolved events of the 1970s in Italy. Giordana's film investigates the 1975 murder of intellectual and director Pier Paolo Pasolini using a variety of media sources, while La prima linea is a fictional reconstruction of particular moments of the terrorist campaign of the group Prima Linea. The article places the films in the context of contemporary Italian cinema's obsession with the return to the 1970s, and examines the use of archive footage as part of a strategy by the filmmakers to negotiate the problematic memories of the period. Finally, it considers the consequences of this return to the archive for thinking about historical memory, postmemory, and the difficult and sometimes tortured dynamic between the present and the past in relation to the 1970s in Italy, and elsewhere